Kinerja Keuangan Industri Kesehatan di Indonesia: Penilaian Metode Economic Value Added (MVA), Financial Value Added (FVA), dan Market Value Added (MVA) - Radja, Firmike Lidyatami (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2024)
EVA is a measure of financial performance by measuring the difference between the company's return on capital and the cost of capital. MVA is used to see the difference between the market value of the company's equity in a certain period and the value of equity supplied by its investors. FVA to measure the contribution of fixed assets in generating profits. The purpose of this study was to determine the financial performance of the health sector listed on the Indonesia Stock Exchange for the 2019-2022 period using the Economic Value Added (EVA), Financial Value Added (FVA) and Market Value Added (MVA) methods. The research method used is quantitative descriptive method with a sample of health sector companies listed on the IDX for the 2019-2022 period. The results of this study indicate that companies in the health sector have positive EVA, FVA and MVA values, meaning that they have good performance and provide added value to shareholders.